Low Intra-Individual Variation in Mean Platelet Volume Over Time in Systemic Lupus Erythematosus - Wirestam, Lina; Gullstrand, Birgitta; Jern, Andreas; Jönsen, Andreas; Linge, Petrus; Tydén, Helena; Kahn, Robin; Bengtsson, Anders A. (Frontiers in Medicine, 2021)
Platelets have recently emerged as important immune modulators in systemic lupus erythematosus (SLE), in addition to their role in thrombosis and cardiovascular disease. However, studies investigating mean platelet volume (MPV) in SLE are often scarce, conflicting and cross-sectional. In this study, MPV was measured in clinical routine throughout a defined time-period to quantify both individual MPV fluctuations and investigate if such variations are associated with disease activity and clinical phenotypes of SLE. Of our 212 patients, 34 patients had only one MPV value reported with the remaining 178 patients having between 2 and 19 visits with recorded MPV values. The intra-individual MPV variation was low, with a median variation of 0.7 fL. This was further supported by the finding that 84% of patients stayed within their reference interval category (i.e. small, normal or large) over time. In our cohort, no correlation between disease activity and MPV neither cross-sectionally nor longitudinally was found. MPV values were significantly smaller in SLE patients (mean 10.5 fL) compared to controls (mean 10.8 fL), p<0.0001. Based on the reference interval, 2.4% (n=5) of patients had large-sized platelets, 84.4% (n=179) had normal-sized and 13.2% (n=28) had small-sized. A larger proportion (85.7%) of patients with small-sized platelets met the anti-dsDNA criterion (ACR10b; p=0.003) compared to patients with normal and large (57.6%) sized platelets. In conclusion, the intra-individual MPV variation was of low magnitude and fluctuations in disease activity did not have any significant impact on MPV longitudinally. This lack of variability in MPV over time indicates that measuring MPV at any time-point is sufficient. Further studies are warranted to evaluate MPV as a possible biomarker in SLE, as well as to determine the underlying mechanisms influencing platelet size in SLE.